The Oxford handbook of publishing - Phillips, Angus, 1961-; Bhaskar, Michael, (Oxford handbooks online., 2019)
Publishing is one of the oldest and most influential businesses in the world. It remains an essential creative and knowledge industry, worth over $140 billion a year, which continues to shape our education and culture. Two trends make this a particularly exciting time. The first is the revolution in communications technology that has transformed what it means to publish; far from resting on their laurels and retreating into tradition, publishers are doing as they always have - staying on the cutting edge. The second is the growing body of academic work that studies publishing in its many forms. Both mean that there has never been a more important time to examine this essential practice and the current state of knowledge.